2021
DOI: 10.1108/hff-10-2020-0669
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydromagnetic and chemical reaction over a stagnation point flow of horizontal stretching/shrinking cylinder in Ag-CuO/water hybrid nanofluid

Abstract: Purpose This paper aims to explore on stagnation point flow of Ag-CuO/water over a horizontal stretching/shrinking cylinder by adding the effect of chemical reaction, B together with the magnetic field, M. Design/methodology/approach A set of reduced ordinary differential equations from the governing equations of partial differential equations is obtained through similarities requirements. The resulting equations are solved using bvp4c in MATLAB2019a. The impact of various physical parameters such as curvatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
(47 reference statements)
2
4
0
Order By: Relevance
“…The numerical results are presented in both table and figures. Table 3 shows the relative values of reduced skin friction coefficient, 𝑓′′(0) when 𝜑 1 = 𝜑 2 = 0 and 𝑀 = 0 with several values of 𝜀, 𝛾 and 𝑃𝑟 = 6.2, which indicates a good correlation between the current results and the results obtained from the previous studies by Najib et al, [30] and Aladdin and Bachok [20]. Thus, it is assured that the present numerical method can be used confidently to solve the fluid flow and heat transfer of the current problem.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…The numerical results are presented in both table and figures. Table 3 shows the relative values of reduced skin friction coefficient, 𝑓′′(0) when 𝜑 1 = 𝜑 2 = 0 and 𝑀 = 0 with several values of 𝜀, 𝛾 and 𝑃𝑟 = 6.2, which indicates a good correlation between the current results and the results obtained from the previous studies by Najib et al, [30] and Aladdin and Bachok [20]. Thus, it is assured that the present numerical method can be used confidently to solve the fluid flow and heat transfer of the current problem.…”
Section: Resultssupporting
confidence: 81%
“…One of the previous studies, as mentioned, is Hayat and Nadeem [28] as the reference for the thermophysical properties of nanoparticles. The range of parameters is taken from the main reference for this study Aladdin and Bachok [20] the required (Ag-CuO/water) hybrid nanofluid with various volume fractions 𝜑 1 = 𝜑 2 = 0.1 is applied to achieve the objectives of this work. Therefore, the nanoparticles volume fraction 𝜑 values are in the range of 0 ≤ 𝜑 ≤ 0.3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature survey presented here, more attention has been set on Porous medium and chemical reaction exposing the problems concerned to porous media that uses the Darcy's relation and chemical reaction. The mass transference influences on MHD oscillatory movement in a porous medium with radiation and chemical reaction were explored by many researchers, as in Ibrahim et al (2015), Sivasankaran et al (2017), Niranjan et al (2016, Adomian (1990), He (2006), He (2003) and Aladdin and Bachok (2022). The effect of magnetic parameter on the unsteady stagnation-point flow and the stability analysis of rear stagnation-point flow of a hybrid nanofluid are analysed by Zainal et al (2022a) and found that the efficiency of heat transfer is significantly impacted by the magnetic factor.…”
Section: Introductionmentioning
confidence: 99%